Did you know that your student that is being long to alphabetize is agitated and inattentive only an oral breather it can be? - Katia Andréia Kühn Chedid; Renata Di Francesco (Universidade Federal de Santa Catarina, 2008)
This article presents another look at a new factor that could interfere with the literacy of children: the oral breathing. Thus, discussions on the key symptoms, biological factors and finally, some considerations that will help us to think improvements to the learning of children do in their initial literacy.